(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background High radiation is a double-edged sword, may be a treatment for some diseases also it may be dangerous when exposed to it in large doses for long periods of time, hospitals are a good example of this, hospitals are cure for patients and at the same time its considered a disease for their workers. Materials and Methods: Giger-Muller instrument counter was used to calculate the level of radioactivity emanating from three hospitals in Babel / Al-Hillah. Radioactivity was measured in different areas of each hospital, especially the X-ray departments, accelerators and CT-scan room. Results: The result is that the data we obtained were within the permissible exposure levels. Determine the most radioactive areas in the study area, the highest value was recorded in (0.90 mSv) in X-ray device in Hilla Surgical Hospital and the lowest dose was (0.015 mSv) in the X-ray device in Imam Al-Sadiq Hospital. Conclusion: Several samples investigated were less than the safe limits recommended by WHO in some respects.